PERKEMBANGAN SOSIO-EMOSIONAL PADA MASA REMAJA - Abdullah, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2019)
Nation’s future is in young generation hand. If we keep a notice of the sentence of course, one decision will be taken that young generation is an expectation for developing and embody welfare and prosperous of the society in this country. For making it true not only science and technology be owned by them. But olso a good attitude and character.